Supraclavicular brachial plexus block in the creation of arteriovenous fistula: a study on microcirculatory changes - Luqman, Khairul Iqaan (2016)
Supraclavicular brachial plexus block (BPB) causes vasodilatation and an increase in blood flow, hence increase the skin perfusion and temperature to the ipsilateral upper limb. However, no reports have comprehensively evaluated these microcirculatory changes after a BPB. To compare the skin perfusion changes before and after supraclavicular BPB and to compare the temperature changes before and after supraclavicular BPB. Thirty two adult patients with chronic renal failure scheduled for AVF surgery were studied in a prospective cross sectional study design. The supraclavicular BPB was performed under ultrasound guidance using 20 mls of levobupivacaine 0.5%. The skin perfusion (AU) and temperature (°C) of both arms were recorded every 5 minutes for 15 minutes pre-block and compared post-block for another 15 minutes, recorded every 5 minutes. To avoid bias, ten healthy adults were recruited for control group and both perfusion and skin temperature of both arms were recorded for 15 minutes. Both skin perfusion and temperature were recorded using Laser Doppler Fluximetry (LDF)machine in both groups. There is a significant difference found between skin perfusion value in anaesthetized arm of studied group (12.80 ± 4.89; P<0.05), but not the contralateral arm (6.25 ± 2.35;P=0.306), before and after a supraclavicular brachial plexus block. There is an increment of 5.46 ± 4.10 AU in the anaesthetized arm, post block. Whereas for the contralateral arm, the increment post block was not significant (0.19 ± 1.04 AU). There is a significant difference found between skin temperature changes in both anaesthetized and contralateral arms of studied group before and after a supraclavicular brachial plexus block. There is an increase in skin temperature in anaesthetized arm (33.36 ± 3.01; P=0.004), as well as contralateral arm (32.16 ± 1.49; P=0.014) of studied group after a supraclavicular brachial plexus block. There were no significant haemodynamic changes post block in all patients (Systolic blood pressure, 153.49 ± 8.34, P=0.061; diastolic blood pressure, 74.89 ± 8.34, P=0.953; heart rate, 74 ± 12, P=0.327). In the control group, there is no significant difference between right arm and left arm in term of skin perfusion and temperature (10.42 ± 2.45, P=0.597 and 27.79 ± 1.01, P=0.896 for skin perfusion and temperature, respectively). Microcirculatory changes that occur after supraclavicular BPB include an increase in skin perfusion and an increase in temperature with stable hemodynamic parameters.